Supporting Historically Underrepresented Groups in STEM Higher Education: The Promise of Structured Mentoring Networks - Markle, Robert S.; Williams, Tyrslai M.; Williams, Kristen S.; deGravelles, Karin H.; Bagayoko, Diola; Warner, Isiah M. (Frontiers in Education, 2022)
Although institutions of higher education have placed a large emphasis on increasing the number of underrepresented minority (URM) students matriculating in higher education, the disparities in STEM retention and graduation rates between URM and non-URM students emphasize the dire need for increased support to help URM students navigate challenges including stereotype threat, impostor phenomenon, and lack of social connectedness that disproportionately affect URM students in majority-dominated fields. Prior research has demonstrated that structured mentoring has the potential to generate substantial improvements in academic, social, and career outcomes for URM STEM students. In particular, network-based mentoring approaches that allow for students to receive both professional and peer mentoring, as well as the opportunity to mentor other students, have demonstrated success in this realm. In this article, we discuss how the current state of academia often fails URM STEM students and faculty, review literature regarding the ways in which structured mentoring approaches can alleviate barriers to success among URM groups in STEM fields, and offer recommendations regarding how academic institutions can successfully implement holistic student and faculty mentoring programs.